Diagnosis and management of allergic rhinitis in children. Issue 12 (18th December 2017) - Noronha, Lizanne; Fox, Adam; Du Toit, George; Lack, Gideon
Abstract : Allergic rhinitis is a very common disease of childhood, and its impact on quality of life is often underestimated. This article discusses the diagnosis of allergic rhinitis in children and the management options that can be tried, including allergen avoidance, pharmacological therapies and allergen immunotherapy.